(3CMGOjK GdTJG , LRA ajg CMGOjK hGQOI aj aUd GdTJGAs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg NGdb GdCRefI hGdaUhd gPG LRA CdaJg aj aUd GdTJG eYJHQ VefJg eG hQO ajg ef GdMOjK GdfHhjs
(3BNQgG (B:s
(3Yf eLGgO Yf YHjO Hf YejQ bGd cGf EPG LGA GdTJG bGd jG Cgd GdbQBf WGd Gddjd dbQCJce abhehG hbUQ GdfgGQ dUjGece aUhehGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs